Metastatic Donor-derived Malignancies Following Simultaneous Pancreas-kidney Transplant: Three Case Reports and Management Strategies. Issue 1 (January 2021) - Amara, Dominic; Wisel, Steven A.; Braun, Hillary J.; Collisson, Eric A.; Friedlander, Terence; Worner, Giulia; Roll, Garret R.; Hirose, Ryutaro; Stock, Peter G.
Abstract : Background: Stopping immunosuppression in a transplant patient with donor-derived malignancy offers the theoretical benefit that reconstitution of the patient's immune system will allow "rejection" of the malignancy, as the malignancy also originates from allogeneic tissue. However, this option exists with the caveat that the patient's allograft(s) will likely be rejected too. In simultaneous pancreas-kidney (SPK) recipients, the normal continued functioning and possible absence of malignancy in either the unaffected kidney or pancreas further complicate this decision. Methods: The charts of 3 patients with donor-derived metastatic malignancies after SPK were retrospectively reviewed in detail. We provide treatment and management recommendations based on successful outcomes and a review of the existing literature. Results: Consistent with a broad review of the literature, in all 3 cases, complete immunosuppression cessation, removal of both grafts, and in 1 case treatment with an immune checkpoint inhibitor to augment the immune response was successful. One patient is doing well 1 year after successfully undergoing kidney retransplantation, while a second patient is active on the waitlist for SPK retransplantation after no evidence of metastatic disease for 2 years. Conclusion: The successful management of metastatic donor-derived malignancies requires allograft removal, immunosuppression cessation, and adjuvant therapy that includes occasional use of checkpoint inhibitors to augment the immune response.